Properties of human asialo-factor VIII. A ristocetin-independent platelet-aggregating agent. - De Marco, L (1981)
Human Factor VIII desialylated by treatment with Vibrio cholerae neuraminidase (ASVIII) aggregated human platelets in the absence of ristocetin in platelet-rich plasma and, to a lesser extent, in washed platelet suspensions. Aggregation is accompanied by thromboxane formation and is completely inhibited by EDTA. Aspirin blocks the second phase of aggregation and abolishes thromboxane production. Subaggregating doses of ASVIII and of either ADP, epinephrine, or collagen produce prompt and complete platelet aggregation. Bernard-Soulier syndrome platelets either did not aggregate with ASVIII (Two cases) or showed markedly decreased aggregation (one cases). Factor VIII complex was prepared from the plasma of two patients with variant von Willebrand's disease (sialic acid content 142 and 75 nmol/mg, respectively); neither protein generated platelet-aggregating activity upon desialylation. [3H]ASVIII binds rapidly to platelets and 37 degrees C, while tritiated, fully sialylated factor VIII binds to a negligible extent. As little as 1--2 micrograms ASVIII bound/10(9) platelets is capable of inducing platelet aggregation. ASVIII may be a useful tool for investigating platelet-Factor VIII interactions in the absence of ristocetin. Furthermore, desialylated Factor VIII might play a physiologic role in Factor VIII-mediated platelet reactions in vivo.